TELAAH TEORITIS: EFEKTIVITAS DAN EFISIENSI DALAM ORGANISASI - Rahmi Widyanti; Basuki Basuki (AL-ULUM : Jurnal Ilmu Sosial dan Humaniora, 2025)
The definition of organization in this paper includes large and small work units such as a department, work unit, project or sub-project. The author assumes that the strength and existence of an organization is highly dependent on the organization's ability to achieve its goals. Therefore, in maintaining, fostering, or developing an organization, it is necessary to pay attention to the effectiveness and efficiency of the organization in achieving the desired goals. Thus, the assessment and measurement of the effectiveness and efficiency of the organization need to be carried out and in this regard, concepts and tools are needed as well as ways to measure the effectiveness and efficiency of the organization.